1995
DOI: 10.1111/j.1365-2362.1995.tb01721.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of IGF‐I and insulin on glucose metabolism, fat metabolism and the cardiovascular system in normal human volunteers

Abstract: The metabolic and cardiovascular effects of recombinant human IGF-I were compared to insulin in six normal subjects. Subjects were studied twice and intravenously received an infusion of [6,6-2H2]glucose (0-480 min) and in random order either IGF-I 20 micrograms kg-1 h-1 (43.7 pmol kg-1 min-1 or insulin 0.5 mU kg-1 min-1 (3.4 pmol kg-1 min-1) with an euglycaemic clamp. One subject was withdrawn following a serious adverse event. During the IGF-I infusion glucose appearance rate (Ra) decreased from 1.79 +/- 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 19 publications
4
36
0
Order By: Relevance
“…It also caused increases in cardiac output, heart rate and stroke volume. Insulin infusion caused similar results, except for decreased NEFAs and no significant changes in cardiovascular variables [283].…”
Section: Glucose Metabolismsupporting
confidence: 55%
“…It also caused increases in cardiac output, heart rate and stroke volume. Insulin infusion caused similar results, except for decreased NEFAs and no significant changes in cardiovascular variables [283].…”
Section: Glucose Metabolismsupporting
confidence: 55%
“…IGF-I shares structural homology and downstream signaling pathways with insulin, and laboratory data have shown that IGF-I has insulin-like effects on peripheral uptake of glucose and fatty acids [1,10]. Further, exogenous administration of recombinant human IGF-I enhances insulin sensitivity in healthy adults [11,12] as well as those with type 2 diabetes [13]. Insulin resistance states including obesity, a strong risk factor for type 2 diabetes, have been associated with altered levels of IGF-I and its binding proteins in circulation [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that this occurs both by stimulation of peripheral glucose utilisation [18] and suppression of hepatic glucose production [19][20][21]. The mechanism of this latter effect is unclear as hepatic expression of the IGF-I receptor is low [22].…”
Section: Rhigf-i and Carbohydrate Metabolismmentioning
confidence: 99%